2015
DOI: 10.1371/journal.pone.0130724
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Food Insecurity among Palestinian Refugees in Lebanon: Data from a Household Survey

Abstract: Lebanon hosts the highest per capita refugee concentration worldwide. The Palestinian presence in Lebanon dates from 1948 and they remain a marginalized population. No information on their food security status has been reported previously. A survey of a representative sample of Palestinian refugee households in Lebanon (n = 2501) was conducted using a stratified two stage cluster sampling approach. We measured food insecurity using a modified USDA household food security module, locally validated. We collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 12 publications
2
33
1
Order By: Relevance
“…The questions take into account participants' culture and value systems when considering their standards of and concerns about the safety of their surroundings. The food security of participating families was assessed with eight items using the Arab Family Food Security scale (AFFS; [37]) plus one supplemental question from the evaluation of the Healthy Kitchens, Healthy Children project, a study in Beirut, Lebanon in which the participants were members of the Palestinian refugee community [23]. The food security questionnaire was developed specifically for Arab communities in the Middle East and measures degrees of family-level food security in the previous year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questions take into account participants' culture and value systems when considering their standards of and concerns about the safety of their surroundings. The food security of participating families was assessed with eight items using the Arab Family Food Security scale (AFFS; [37]) plus one supplemental question from the evaluation of the Healthy Kitchens, Healthy Children project, a study in Beirut, Lebanon in which the participants were members of the Palestinian refugee community [23]. The food security questionnaire was developed specifically for Arab communities in the Middle East and measures degrees of family-level food security in the previous year.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, food insecurity has been linked to poor mental health (self-reported using the five-item Mental Health Inventory) in a representative sample of Palestinian refugee households in Lebanon [23]. Using the same dataset, Habib and colleagues [24] found that adults in crowded households (calculated by dividing the number of people in a home by the number of rooms, excluding the balcony, kitchen, and restrooms; above the median of 1.69 people per room was considered crowded) were more likely to report poor health outcomes-including mental health, chronic and acute illnesses, and disability-compared with those living in homes without crowding.…”
Section: Competing Interestsmentioning
confidence: 99%
“…This category covered 8 studies 17,[20][21][22][23]25,27,28 which presented aspects related to social, cultural, political and economic difficulties of access to food in refugee detention centers, refugee camps and in settlement destination countries.…”
Section: Food Inequitymentioning
confidence: 99%
“…In addition, the findings suggest that families of refugees with members with incapacitating physical disabilities are at greater risk of food shortages, and consequently food insecurity. Although the studies point to the existence of humanitarian assistance, it also points out that this is insufficient to address barriers to food access 20,23 . Studies A14 and A17 present food and nutrition aspects of Saharan refugees living in refugee camps in Algeria.…”
Section: Food Inequitymentioning
confidence: 99%
“…23 Food insecure Palestinian refugees were found to have reduced diet quality, and to resort to eating less and cheaper food and borrowing or receiving money or food. 18 The right to food, and the rights of people with disabilities are both key human rights issues, and establishing causal links between the two could contribute to establishing an evidence base that can inform future programs and policies to reduce avoidable nutrition-related disability, 2 particularly in vulnerable populations such as refugees.…”
mentioning
confidence: 99%